Vitamin Pb2s : new perspectives in painting. - Phaidon Press (London : Phaidon, 2011)
This edition includes 115 artists from over thirty countries who represent the best of the new international painting.
'Everyday painting' / Barry Schwabsky --Nina Chanel Abney --Richard Aldrich --Ellen Altfest --Hurvin Anderson --Karin Mamma Andersson --Juan Araujo --Tauba Auerbach --Jules de Balincourt --Antonio Ballester Moreno --Hernan Bas --Tilo Baumgartel --Micael Borremans --Mark Bradford --Kerstin Bratsch --Lisa Brice --Rafal Bujnowski --Stephen Bush --Varda Caivano --Brian Calvin --Gillian Carnegie --Sarah Crowner --William Daniels --Noah Davis --Philippe Decrauzat --Benjamin Degen --Kaye Donachie --Pierre Dorion --Milena Dragicevic --Thomas Eggerer --Nicole Eisenman --Ida Ekblad --Michael Fullerton --Adrian Ghenie --Wayne Gonzales --Mark Grotjahn --Wade Guyton --Josephine Halvorson --N. S. Harsha --Richard Hawkins --Carmen Herrera --Alex Hubbard --Jacqueline Humphries --Nathan Hylden --Merlin James --Xylor Jane --Jia Aili --Magdalena Jitrik --Chantal Joffe --Chris Johanson --Tish Kallat --Maki Na Kamura --Jacob Kassay --Khalif Kelly --Martin Kobe --Jutta Koether --Tomasz Kowalski --Makiko Kudo --Stefan Kurten --Li Dafang --Li Shurui --Li Songsong --Liang Yuanwei --Liu Xiaodong --Marcin Macie Jowski --Tala Madani --Nalini Malani --Victor Man --I nyoman Masriadi --Birgit Megerle --Dianna Molzan --Katy Moran --Kristine Moran --Justin Mortimer --Farhad Moshiri --Surendran Nair --Odili Donald Odita --Paulina Olowska --Christopher Orr --Silke Otto-Knapp --Alessandro Pessoli --Jon Pestoni --Johannes Phokela --Vitaly Pushnitsky --R. H. Quaytman --Blake Rayne --Clare Rojas --Sterling Ruby --Christoph Ruckhaberle --Serban Savu --Maaike Schoorel --Diana Schultz --Raoib Shaw --Amy Sillman --Anj Smith --Josh Smith --Glenn Sorensen --Neal Tait --Mickalene Thomas --Madraig Timoney --Alexander Tinei --Phoebe Unwin --Lesley Vance --Pieter Vermeersch --Charline Von Heyl --Kelley Walker --Wang Xingwei --Corinne Wasmuht --Matthias Weicher --Andro Wekua --Wendy White --Katharina Wulff --Lynette Yiadom-Boakye --Luiz Zerbine --Zhang Enli --Jakub Jukian Ziolkowkski.
Includes bibliographical references and index.
Keywords: Painting; Painting, Modern -- 20th century; Painting, Modern -- 21st century; Artists -- Biography